El fuste de la democracia liberal sigue siendo demasiado recto - Requejo, Ferran (Foro Interno, 2010)
This article analyzes the difficulties that liberal democracies face in accommodating a diversity of values, interests and identities in contexts of national pluralism (plurinational states). The first section analyzes the fallacy of abstraction and the distortions of the concept of pluralism that occur in enlightenment-based theories. The second section begins with a brief description of three classic institutional solutions for accommodating plurinational societies in liberal democracies: federalism, consociationalism and secession. A comparative analysis of nineteen decentralized federal or regional democracies is then discussed in order to evaluate the adequacy of federalism in regulating political recognition and accommodation in contexts of national pluralism. My conclusion suggests that these two objectives can only be achieved by means of plurinational federalism or partnership, which may also include consociational processes that regulate the possible secession of minority nations.